SOME IMMUNOLOGICAL INDICATORS IN INFANTS WITH PSYCHOMOTOR DEVELOPMENT RETARDATION IN CONSEQUENCE OF CENTRAL NERVOUS SYSTEM HYPOXIC-ISCHEMIC PERINATAL DAMAGE - Kh.M. Karimova; L.S. Namazova-Baranova; A.M. Mamed"yarov; T.V. Turti; T.P. Klyushnik (Педиатрическая фармакология)
Despite the fact that there are the researches testifying to activation of congenital (nonspecific) and got (adaptive, specific) immunity in Central Nervous System Perinatal Damages, interrelations between blood sera immunological indicators and clinical lines of Central Nervous System Perinatal Damages are studied now insufficiently. In our work the analysis of interrelations between a number of immunological indicators (the activity of leucocyte elastase (LE) and 1-proteinase inhibitor (α1-PI), the rates of autoantibodies (aAB) to nerve tissue proteins) and psychomotor development of children with consequences of Central Nervous System hypoxic-ischemic Perinatal Damages has been carried out. It is revealed that in this pathology activation of the congenital and got immunity takes place; the congenital immunity activation degree (on LE activity) back correlates with severity of psychomotor development disorders, activity α1-PI directly correlates with a psychomotor development point of children, i.e. its lowered activity is the adverse diagnostic factor; joining of autoimmune reactions (increased rates of aAB to nerve tissue proteins) characterizes the heaviest variants of psychomotor development retardations. It is shown also that pre-term infants have lower point of psychomotor development, and also more patients of this group have low α1-PI activity and the raised levels of aAB in comparison to full-term infants.Key words: children, perinatal damages of central nervous system, psychomotor development, congenital immunity, leucocyte elastase, α1-proteinase inhibitor, autoimmune reactions.